ONTOLOGICAL FRAMEWORK OF ISLAMIC STUDIES: A PHILOSOPHICAL REVIEW OF THE RELATIONSHIP BETWEEN REVELATION AND REASON IN CONTEMPORARY ISLAMIC THOUGHT DISCOURSE - Rifki Alfauzi; Siti Mahmudah Noorhayati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The ontology of Islamic studies is a philosophical foundation that serves to explain the essence of Islam in its transcendental, humanitarian, cosmological, and socio-historical dimensions. This study uses a qualitative approach with a philosophical analysis of the latest literature from the past five years. The discussion focuses on the definition of the ontology of Islamic studies, its scope and object of study, the relationship between revelation and reason, and its relevance in the contemporary era. The results of the study indicate that the ontology of Islamic studies positions revelation as an absolute source of knowledge that synergizes with reason to present an integrative and contextual scientific paradigm. In the contemporary era, the ontology of Islamic studies is relevant in strengthening the identity of Islamic scholarship, building ethics in the development of science and technology, and providing solutions to problems in education, morality, and socio-religious matters. Thus, this study confirms that the ontology of Islamic studies is not only theoretical but also applicable in addressing global challenges.